Perovskite KNi0.8Co0.2F3 nanocrystals for supercapacitors. Issue 34 (16th August 2017) - Ding, Rui; Li, Xudong; Shi, Wei; Xu, Qilei; Han, Xiuli; Zhou, Yong; Hong, Weifeng; Liu, Enhui
Abstract : Perovskite KNi0.8 Co0.2 F3 nanocrystal-based supercapacitors delivered high power and energy densities together with excellent cycle life. Abstract : Perovskite KNi0.8 Co0.2 F3 nanocrystals were introduced as potential electrode materials for supercapacitors, which exhibited superior specific capacity and rate behavior owing to the optimal synergistic effect of Ni and Co redox species. The AC//KNi0.8 Co0.2 F3 asymmetric capacitor delivered high power and energy densities together with excellent cycling stability.